Fast ultrahigh-density writing of low-conductivity patterns on semiconducting polymers - Farina, Marco; Ye, Tengling; Lanzani, Guglielmo; di Donato, Andrea; Venanzoni, Giuseppe; Mencarelli, Davide; Pietrangelo, Tiziana; Morini, Antonio; Keivanidis, Panagiotis E. (My University, 2013)
The exceptional interest in improving the limitations of data storage, molecular electronics and optoelectronics has promoted the development of an ever increasing number of techniques used to pattern polymers at micro and nanoscale. Most of them rely on atomic force microscopy to thermally or electrostatically induce mass transport, thereby creating topographic features. Here we show that the mechanical interaction between the tip of the atomic force microscope and the surface of π-conjugated polymeric films produces a local increase of molecular disorder, inducing a localized lowering of the semiconductor conductivity, not associated to detectable modifications in the surface topography. This phenomenon allows for the swift production of low-conductivity patterns on the film surface at a speed exceeding 20 μm s⁻¹; paths have a resolution in the order of the tip size (20 nm) and are detected by a conducting-atomic force microscopy tip in the conductivity maps.
Keywords: Single Cell Protein; Microfluidic; Antibody Microarray